PENGARUH IKLAN, PROMOSI DAN HARGA TERHADAP EKUITAS MEREK - Andi Irwan; Kamaruddin (STIM LPI Makassar, 2023)
Marketing communications may provide the means for developing strong, customer-based brand equity. Among marketing communication tools, advertising and price promotion have always played a pivotal role. Hence, this research examines the effect of perceived advertising spending and price promotion on brand equity across experience goods/services. Jean was chosen as goods because it’s quality can be judged well before and after purchase or use it and bank was chosen as experience products due to its quality is unable to judge before use and able to judge quality after use. This research finds that advertising has significant positive impact on brand equity for both goods product and experience product. However, price promotion, for goods product, has significant negative impact on brand awareness and brand association and, for experience product (banking service), has positive effect on perceived quality and brand loyalty. In order to build strong brand equity effectively, managers must invest in the advertising but considering product categories when applying price promotion.